Syntheses, crystal structures and MMCT properties of cyanide-bridged binuclear Ru–Fe complexes. (15th November 2019) - Li, Su-Hua; Liu, Yang; Yang, Yu-Ying; Zhang, Yu-Xiao; Xu, Qing-Dou; Hu, Sheng-Min; Wu, Xin-Tao; Sheng, Tian-Lu
Graphical abstract: Two new binuclear mixed-valence compounds and their one-electron oxidation products, [MeCpLRu(μ-CN)Fe(dppe)Cp][PF6 ] n (L = dppe, (PPh3 )2 ) ( n  = 1, 2), were synthesized and thoroughly characterized by single-crystal X-ray diffraction analysis. Complexes 1 2+ and 2 2+ are one-electron oxidation products of 1 1+ and 2 +, respectively. The electronic absorption results indicate that there exists metal to metal charge transfer (MMCT) in the one-electron oxidation products, which is strongly supported by the theoretical calculations. Complexes 1 2+ and 2 2+ can be defined as Class II MV compounds. It is found that the MMCT band is obviously red-shifted on going from 1 2+ to 2 2+, because the donating electron ability of (PPh3 )2 is stronger than that of dppe. Abstract: In this report, two new binuclear mixed-valence (MV) compounds and their one-electron oxidation products, [MeCpLRu(μ-CN)Fe(dppe)Cp][PF6 ] n (L = dppe, (PPh3 )2 ) ( n  = 1, 2), were synthesized and thoroughly characterized by single-crystal X-ray diffraction analysis. Complexes 1 2+ and 2 2+ are one-electron oxidation products of 1 1+ and 2 +, respectively. The electronic absorption results indicate that there exists metal to metal charge transfer (MMCT) in the one-electron oxidation products, which is strongly supported by the theoretical calculations. Complexes 1 2+ and 2 2+ can be defined as Class II MV compounds. It is found that the MMCT band is obviously red-shifted on going from 1 2+ to 2 2+, because the donating electron ability of (PPh3 )2 is stronger than that of dppe.